Third place: a qualitative examination of socialization and community building in CCRCs - Ellis, Jared Paul, author; Malinin, Laura, advisor; Scolere, Leah, advisor; Cross, Jeni, committee member (Colorado State University. Libraries, 2020)
Continuing Care Retirement Communities (CCRCs) continue to be a popular option for senior living. Social activity is invariably tied to improved health trajectories and decreased loneliness but is often challenging for persons who may not have transportation available pointing at designers and architects to create quality social spaces within the CCRC itself. The concept of Oldenburg's third place and the breadth of literature tied to it provides a link between the built environment and network sociology informing this study. This case study utilized a spatial inventory, resident interviews and direct observations to investigate 1) whether CCRCs are utilizing Evidence-based design (EBD), 2) if there are naturally occurring or purpose-build third places internal to the community, and 3) whether these spaces were supporting socialization for the residents. While findings indicated limited use of EBD principals, the use of administrative policy lead to unique social leveling in the CCRC's purpose-built third place.
Keywords: interior design; seniors; third place; senior living; CCRC; socialization